2010
DOI: 10.1038/ncomms1043
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain protects against adverse developmental programming of the kidney

Abstract: The kidney is extraordinarily sensitive to adverse fetal programming. Malnutrition, the most common form of developmental challenge, retards the formation of functional units, the nephrons. The resulting low nephron endowment increases susceptibility to renal injury and disease. Using explanted rat embryonic kidneys, we found that ouabain, the Na,K-ATPase ligand, triggers a calcium–nuclear factor-κB signal, which protects kidney development from adverse effects of malnutrition. To mimic malnutrition, kidneys w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 43 publications
1
76
1
Order By: Relevance
“…Notably, our results are in complete accord with those of Li et al, who studied the influence of ouabain administration to pregnant animals. 14 The increase in maternal ouabain in rats subjected to the stressful condition of a low-protein diet in the study by Li et al rescued the development of the offsprings' kidneys, and the reduction in the endogenous steroid during normal mouse pregnancy, described here, impaired kidney growth. Therefore, increased maternal ouabain has a protective effect on the kidney, whereas a reduction in the steroid level has a deleterious consequence.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Notably, our results are in complete accord with those of Li et al, who studied the influence of ouabain administration to pregnant animals. 14 The increase in maternal ouabain in rats subjected to the stressful condition of a low-protein diet in the study by Li et al rescued the development of the offsprings' kidneys, and the reduction in the endogenous steroid during normal mouse pregnancy, described here, impaired kidney growth. Therefore, increased maternal ouabain has a protective effect on the kidney, whereas a reduction in the steroid level has a deleterious consequence.…”
Section: Discussionmentioning
confidence: 72%
“…Studies by Li et al showed that the addition of exogenous ouabain to pregnant rats rescues the development of embryonic kidneys in animals given a low-protein diet, suggesting the steroid's role in kidney development. 14 In view of these studies, we hypothesized that circulating ouabain in normal pregnant animals may have a protective effect on the offsprings' development and growth, particularly of the kidney. To test this hypothesis, we examined the effect of a reduction in circulating maternal ouabain on the weight of the offspring and their tissues.…”
mentioning
confidence: 99%
“…32 The calcium oscillations triggered by ouabain/Na,K-ATPase/IP3R signaling have a frequency of approximately 1 peak every 3-5 minutes, and calcium oscillations with this periodicity have previously been reported to activate NF-kB. [16][17][18][19] Here we showed that ouabain signaling triggers activation and translocation of NF-kB p65 subunit to the nucleus in cells exposed to Stx2 and ouabain but found no evidence of NF-kB p65 subunit activation in cells exposed to Stx2 alone. Helenalin inhibits the transcriptional effect of NF-kB p65 subunit; in cells co-incubated with Stx2, ouabain, and helenalin, the capacity of ouabain to protect against apoptosis was lost.…”
Section: Discussionmentioning
confidence: 97%
“…The signaling pathway involves interaction between Na,K-ATPase and the inositol 1,4,5-triphosphate receptor (IP3R), triggering of slow intracellular calcium oscillations, and activation of the NF-kB p65 subunit (or RelA). [16][17][18][19] Because NF-kB p65 is known to increase the expression of Bcl-xL, 20 we hypothesized that ouabain-triggered Na,K-ATPase signaling may counteract the apoptotic action of Stx2 by upregulation of Bcl-xL and downregulation of Bax. Here we present a series of studies in support of this hypothesis.…”
mentioning
confidence: 99%
“…69 This observation led us to hypothesize that the antiapoptotic effect of ouabain/Na + ,K + -ATPase/IP3R signaling might rescue development of the malnourished fetal kidney. 70 To test this hypothesis, we performed a study on E14 embryonic rat kidney explant cultures. The kidneys were cultured for 3 days, and to mimic malnutrition, serum concentration in the medium in which the kidneys were grown was reduced from 10% to 0.5% from the second day.…”
Section: Slow Calcium Oscillations Activate Nf-kb and Protect From Apmentioning
confidence: 99%